METHODOLOGY OF TRAFFIC MASKING IN A SPECIALIZED DATA TRANSMISSION NETWORK - Klimovych, Serhii (Ukrainian Information Security Research Journal, 2023)
In connection with the growing threats in cyber security, there is a need to develop new approaches and methodologies for masking traffic to avoid detection and analysis of traffic by unauthorized persons. Traffic masking allows you to hide the characteristics of the transmitted data, such as source, destination, type and volume, path, and other metadata that make it possible to identify and analyze the communication. This can be particularly useful in cases where it is necessary to preserve the privacy of users or to prevent disclosure of sensitive information. Modern methods of traffic analysis are constantly being improved, so there is a need to develop new approaches to masking in accordance with changes in data analysis technologies. The relevance of the work is related to the fact that the actions of the administrator of a specialized network to ensure the security of its operation are aimed at solving two interrelated tasks, namely: ensuring the hidden functioning of the network and detecting facts of third-party intervention (detecting the actions of outsiders). Both tasks are strictly regulated by the governing documents, but the final result depends on the official’s depth of understanding of the existing problem, the degree of mastery of the methodology for ensuring the security of the functioning of a specialized network, the available material (including financial) means and the available time resource. The paper analyzes the existing approaches to ensuring traffic masking in the network, provides algorithms (software implementation options) of masking mechanisms and detection of the fact of traffic masking in a specialized data transmission network.